Global, regional, and national economic burden of hematologic malignancies (1990–2021) with projections to 2050 - Zhexian Li; Guangpeng Chen; Guibin Du (Frontiers in Public Health)
BackgroundHematologic malignancies (HM) impose substantial healthcare and productivity-related costs globally. However, disparities in economic impact across regions and countries remain insufficiently explored. This study aimed to evaluate the global, regional, and national economic burden of HM and its subtypes (leukemia, non-Hodgkin lymphoma, multiple myeloma, and Hodgkin lymphoma) from 1990 to 2021, with projections to 2050.MethodsData from the Global Burden of Disease 2021 study were utilized to estimate the economic burden of HM using the value of a statistical life year (VSLY) approach, based on disability-adjusted life years (DALYs). Decomposition analysis was conducted to identify drivers of economic burden, including population growth and aging. Future trends were modeled using the Bayesian Age-Period-Cohort (BAPC) model, and comparisons of economic burden were made across countries by income levels.ResultsIn 2021, the global economic burden of HM reached $1.516 trillion, a 52.8% increase from $992 billion in 1990. This represented approximately 1% of the global GDP, with high-income countries (HICs) bearing the largest share of 2.17% of GDP, compared to 0.58% in lower-middle-income countries (LMICs). The United States had the highest national burden at $417.42 billion (95% UI: $389.49–$435.80 billion), followed by China $133.84 billion (95% UI: $98.63–$166.21 billion), $113.03 billion (95% UI: $101.62–$122.88 billion), and Japan $88.30 billion (95% UI: $85.65–$90.24 billion). By 2050, the global burden is projected to decline to $1.249 trillion, driven by healthcare advancements in HICs, but with a rising burden in upper-middle-income countries (UMICs), which are expected to account for 48.1% of the global burden. China is projected to lead globally with $421.65 billion (95% UI: $314.68–$1,495.35 billion), followed by India ($123.8 billion), while the United States is expected to decline to $101.6 billion. Subtype-specific analysis revealed that Leukemia accounted for the largest proportion of the burden in 2021 ($651 billion, 42.9%), followed by NHL ($492 billion, 32.5%), multiple myeloma ($278.17 billion, 100.5%), and Hodgkin lymphoma ($43.84 billion, 21%).ConclusionsThe economic burden of HM has increased significantly, with marked disparities across regions and income levels. By 2050, the burden is expected to shift from high- to middle-income countries. Investments in early diagnosis, affordable treatments, and healthcare improvements are essential to reduce the burden and address inequities.